Analysis of brain and spinal cord lesions to occult brain damage in seropositive and seronegative neuromyelitis optica. Issue 94 (September 2017) - Sun, Jie; Sun, Xianting; Zhang, Ningnannan; Wang, Qiuhui; Cai, Huanhuan; Qi, Yuan; Li, Ting; Qin, Wen; Yu, Chunshui
Abstract: Objectives: According to aquaporin-4 antibody (AQP4-Ab), neuromyelitis optica (NMO) can be divided into seropositive and seronegative subgroups. The purpose of this study was to a) compare the distribution of spinal cord and brain magnetic resonance imaging (MRI) lesions between seropositive and seronegative NMO patients; b) explore occult brain damage in seropositive and seronegative NMO patients; and c) explore the contribution of visible lesions to occult grey and white matter damage in seropositive and seronegative NMO patients. Materials and methods: Twenty-two AQP4-Ab seropositive and 14 seronegative NMO patients and 30 healthy controls were included in the study. Two neuroradiologists independently measured the brain lesion volume (BLV) and the length of spinal cord lesion (LSCL) and recorded the region of brain lesions. The normal-appearing grey matter volume (NAGM-GMV) and white matter fractional anisotropy (NAWM-FA) were calculated for each subject to evaluate occult brain damage. Results: The seropositive patients displayed more extensive damage in the spinal cord than the seronegative patients, and the seronegative group had a higher proportion of patients with brainstem lesions (28.57%) than the seropositive group (4.55%, P = 0.064). Both NMO subgroups exhibited reduced NAGM-GMV and NAWM-FA compared with the healthy controls. NAGM-GMV was negatively correlated with LSCL in the seropositive group (rs = −0.444, P = 0.044) and with BLV in the seronegative group (rs = −0.768, P = 0.002). NAWM-FA was also negatively correlated with BLV in the seropositive group (rs = −0.682, P < 0.001). Conclusion: Our findings suggest that the occult brain damage in these two NMO subgroups may be due to different mechanisms, which need to be further clarified.